IEEE INFOCOM 2019 - IEEE Conference on Computer Communications Workshops (INFOCOM WKSHPS) 2019
DOI: 10.1109/infcomw.2019.8845115
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Stage Classification Using Bidirectional LSTM in Wearable Multi-sensor Systems

Abstract: Understanding the sleep quality and architecture is essential to human being's health, which is usually represented using multiple sleep stages. A standard sleep stage determination requires Electroencephalography (EEG) signals during the expensive and labor-intensive Polysomnography (PSG) test. To overcome this inconvenience, cardiorespiratory signals are proposed for the same purpose because of the easy and comfortable acquisition by simplified devices. In this paper, we leverage our low-cost wearable multi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 26 publications
(33 reference statements)
1
10
0
Order By: Relevance
“…Results show that the average accuracy of the 240 participants was 81.16%, which is a similar level of the accuracy estimated by medical experts [59]. However, N1 stage is poorly detected compared with the other stages that have been consistently addressed in the previous reports [62], and the N1 and N2 sleep stages are usually considered as one stage, 'Light sleep' [27] in four-sleep stage taxonomy [92][93][94][95][96][97]. We also applied the four stage scheme with combining the N1 and N2 stage as one 'Light sleep' to analyze the sleep quality in multiple approaches.…”
Section: Sleep Stage Automation Evaluationsupporting
confidence: 56%
“…Results show that the average accuracy of the 240 participants was 81.16%, which is a similar level of the accuracy estimated by medical experts [59]. However, N1 stage is poorly detected compared with the other stages that have been consistently addressed in the previous reports [62], and the N1 and N2 sleep stages are usually considered as one stage, 'Light sleep' [27] in four-sleep stage taxonomy [92][93][94][95][96][97]. We also applied the four stage scheme with combining the N1 and N2 stage as one 'Light sleep' to analyze the sleep quality in multiple approaches.…”
Section: Sleep Stage Automation Evaluationsupporting
confidence: 56%
“…Several recent studies have used wearable devices to estimate sleep quality and sleep-related parameters [15][16][17][18] and analyzed the relationship between sleep and depression [19][20][21]. Miwa et al [19] estimated sleep quality by detecting rollover movements during sleep and observed a significant difference in sleep quality between nondepressed and depressed people.…”
Section: Introductionmentioning
confidence: 99%
“…The algorithms deployed on the system included signal quality evaluation, signal processing, real-time abnormal event monitoring and early prediction, and patients’ health assessment, which were packaged as a toolkit (Midas). The accuracy, stability, and effectiveness of our system have been validated in previous studies [ 44 - 46 ].…”
Section: Methodsmentioning
confidence: 86%